Factors Influencing the performance of agricultural extension services on women farmer groups in Luwu Regency, Indonesia - Besse Amisnawati; Syafruddin (Jurnal Ilmiah Pertanian, 2023)
Agricultural extension services (PPL) have the task of counseling farmers and farmer groups to improve their welfare. One of the farmer groups that became the counseling target was the women farmer groups (KWT). This study aimed to analyze the performance of agricultural extension services in the Women Farmer Group (KWT) in Bajo District, Luwu Regency, South Sulawesi, and the influence of personal characteristics, group environment, and social environment on the performance of extension workers. The research method used in this study was a quantitative approach with a descriptive and explanatory design. The research population was KWT members in the Bajo District using a saturated sample in which all populations become respondents. Data analysis used the Varian-Based Structural Equation Modeling (VB-SEM) analysis technique with Smart PLS 3.0 application. The results showed that the performance level of the extension worker was 72.02 on a scale of 10 to 100. Personal characteristics, group environment, and social environment significantly influenced the performance of the extension worker. In this case, to improve their performance, extension services need to encourage the involvement of farmer group members in all stages of extension activities. In addition, extension services need to improve the dynamics of farmer groups to be more developed and dynamic so that members can benefit from the group. Furthermore, extension services need to continue to establish harmonious social relations with the surrounding environment to create conditions conducive to farmer groups' activities and the implementation of extension activities.